2018
DOI: 10.1002/lary.27730
|View full text |Cite
|
Sign up to set email alerts
|

Cortical networks for speech motor control in unilateral vocal fold paralysis

Abstract: Objective To evaluate brain networks for motor control of voice production in patients with treated unilateral vocal fold paralysis (UVFP). Study Design Cross‐sectional comparison. Methods Nine UVFP patients treated by type I thyroplasty, and 11 control subjects were compared using magnetoencephalographic imaging to measure beta band (12–30 Hz) neural oscillations during voice production with perturbation of pitch feedback. Differences in beta band power relative to baseline were analyzed to identify cortical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…Changes in vocal pitch relative to pre‐shift baseline were calculated as Cents = 1200 × log 2 (pitch/mean baseline). Reponses to upward pitch‐shifts were flipped such that any compensatory response opposite the shift was positive (and any imitation downward) 21, 30 . Calculations were complicated by the presence of vocal tremor in a number of subjects (Table I), which lead to significant variability in pitch compensation measurements due to perturbations beginning at random phases of the 4 Hz to 5 Hz tremor 31 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in vocal pitch relative to pre‐shift baseline were calculated as Cents = 1200 × log 2 (pitch/mean baseline). Reponses to upward pitch‐shifts were flipped such that any compensatory response opposite the shift was positive (and any imitation downward) 21, 30 . Calculations were complicated by the presence of vocal tremor in a number of subjects (Table I), which lead to significant variability in pitch compensation measurements due to perturbations beginning at random phases of the 4 Hz to 5 Hz tremor 31 .…”
Section: Methodsmentioning
confidence: 99%
“…Due to the presence of SD‐related vocal breaks, there were significant outlying pitch measurements on most trials. While such trials are often excluded in these sort of experiments, 30 doing so here would have eliminated most trials. We, therefore, chose to use median rather than mean pitch contours for these analyses, and selected the peak from this by visual inspection of the averaged waveform.…”
Section: Methodsmentioning
confidence: 99%
“…The DSP was implemented on a PC as a real-time vocoder program called Feedback Utility for Speech Processing (FUSP) 38,[40][41][42] .…”
Section: Meg Imaging and Experimental Designmentioning
confidence: 99%
“…To correct for multiple comparisons across time and space, corrected p-value thresholds were calculated for = 0.05 and a False Discovery Rate (FDR) of 5%. Furthermore, cluster correction was performed to exclude clusters with less than 18 congruent voxels as done in previous studies 40 .…”
Section: Meg Data Processingmentioning
confidence: 99%
“…Long‐term expectation mismatch in voice production may drive observable change to networks in the brain that are involved in judgment of voice‐as‐self or self‐referential behavior. A recent magnetoencephalography imaging (MEGI) pilot study in UVFP patients expertly treated by type I thyroplasty revealed enhanced β‐band oscillatory activity in the medial frontal brain region . This particular region is a constitutive component of the default mode network (DMN), a large‐scale interconnected network of brain regions that is broadly active during self‐referential behavior and can be examined using resting‐state functional magnetic resonance imaging (RS‐fMRI) .…”
Section: Introductionmentioning
confidence: 99%